Evaluating Explainable Artificial Intelligence Methods for Interpretable Machine Learning Models in Large Scale Enterprise Data Analytics Systems - Indra Ava Dianta; Greget Widhiati; Andreas Tigor Oktaga (Asosiasi Pengelola Jurnal Informatika dan Komputer Indonesia, 2026)
Explainable Artificial Intelligence (XAI) has become a critical area of research within artificial intelligence, focusing on improving the transparency and interpretability of machine learning (ML) models, often referred to as